Relay precoding for dual-hop MIMO network using per antenna SLNR maximization - Saand, A.S. (IEEE Computer Society, 2014)
In this paper, we consider a dual-hop multipleinput-multiple-output (MIMO) half-duplex amplify-and-forward relay network. Each terminal is equipped with multiple antennas. A novel and efficient precoding scheme based on per-antennasignal to leakage plus noise ratio (PA-SLNR) maximization is used at the relay downlink. We consider linear processing only at the relay terminal. The channel state information of first and second hop channel is assumed at the relay terminal. QR decomposition with successive interference cancellation is utilized at the user end as the detection scheme. Monte Carlo simulation confirms better performance in terms of ergodic capacity offered by the proposed scheme. Â© 2014 IEEE.